Decoding Silence in Digital Cross-Cultural Communication: Overcoming Misunderstandings in Global Teams - Hayati, Daryoosh; Sinha, Shriya (WISE Pendidikan Indonesia, 2024)
This study investigates the role of silence in digital cross-cultural communication, emphasizing its potential for misinterpretation due to cultural differences and the absence of non-verbal cues. Silence, often perceived differently across high- and low-context cultures, plays a crucial role in conveying emotions and intentions. In digital spaces, the lack of immediate feedback and non-verbal richness increases the complexity of silence interpretation. This research employs a comprehensive literature review to explore how silence is used in virtual communication platforms like Zoom and Slack and its impact on global teams. The study analyzes various existing research on silence in intercultural communication and digital communication tools. Key findings reveal that silence in high-context cultures, such as Japan and China, is seen as reflective and respectful, while in low-context cultures like the United States, it is often interpreted negatively, leading to miscommunication. Furthermore, the absence of non-verbal cues in digital environments exacerbates these misunderstandings. The study also explores the potential of emerging technologies like artificial intelligence (AI) to mitigate these communication barriers by detecting and interpreting silence more effectively. The results underscore the need for cultural sensitivity in virtual teams and highlight the limitations of current AI tools in understanding cultural nuances. This research contributes to the ongoing discourse on improving intercultural communication in digital settings, offering practical implications for global teams and suggesting future directions for AI integration in digital communication platforms.